2017
DOI: 10.1111/bjh.14757
|View full text |Cite
|
Sign up to set email alerts
|

Serological weak D phenotypes: a review and guidance for interpreting the RhD blood type using the RHD genotype

Abstract: Summary Approximately 0.2% to 1% of routine RhD blood typings result in a “serological weak D phenotype.” For more than 50 years, serological weak D phenotypes have been managed by policies to protect RhD-negative women of child-bearing potential from exposure to weak D antigens. Typically, blood donors with a serological weak D phenotype have been managed as RhD-positive, in contrast to transfusion recipients and pregnant women, who have been managed as RhD-negative. Most serological weak D phenotypes in Cauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 87 publications
(107 reference statements)
4
101
0
5
Order By: Relevance
“…The molecular testing used in this study also affirmed the current algorithm used for serological detection of weak D types in the population of blood donors. Serological methods depend on immunohematological technique and test reagents are not capable of always unequivocally detecting RhD variants (weak D, such as weak D type 11, partial D or DEL) [38]. Therefore, RHD molecular typing is recommended to identify and confirm RHD variants [39].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular testing used in this study also affirmed the current algorithm used for serological detection of weak D types in the population of blood donors. Serological methods depend on immunohematological technique and test reagents are not capable of always unequivocally detecting RhD variants (weak D, such as weak D type 11, partial D or DEL) [38]. Therefore, RHD molecular typing is recommended to identify and confirm RHD variants [39].…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, the anti-RH5 antibodies associated with these molecular backgrounds are auto-antibodies, and patients are therefore no more prone to the formation of anti-RH4 or anti-RH5 antibodies when exposed to non-genotype-matched pRBCs. The status of the RH1 antigen associated with weak D type 4.0 (RHD*09.03) is also under scrutiny [41,42,43]. …”
Section: Part Ii: Review Of the French Strategy At Lihm Créteil Betwementioning
confidence: 99%
“…We have observed that when the molecular report does not provide an interpretation and recommendation, clinical practictioners not experienced in blood group genetics hesitate to interpret RHD genotyping results as D+ or D−. For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history as well as the current evolving data and literature reports of the risks for alloimmunization associated with specific RHD genotypes . Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.…”
Section: Guidance For Managing Transfusion or Rhig Administration In mentioning
confidence: 99%
“…For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history 2,5 as well as the current evolving data 6-22 and literature reports 15,16,[23][24][25][26] of the risks for alloimmunization associated with specific RHD genotypes. 27 Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.We provide guidance on the interpretation and update our previous recommendation 2 to include the management ABBREVIATIONS: ACOG = American College of Obstetricians and Gynecologists; RhIG = Rh immune globulin.…”
mentioning
confidence: 99%
See 1 more Smart Citation